2010
DOI: 10.1021/la103732r
|View full text |Cite
|
Sign up to set email alerts
|

Surface Structural Evolution in Iron Oxide Thin Films

Abstract: Ordered iron oxide ultrathin films were fabricated on a single-crystal Mo(110) substrate under ultrahigh vacuum conditions by either depositing Fe in ambient oxygen or oxidizing preprepared Fe(110) films. The surface structure and electronic structure of the iron oxide films were investigated by various surface analytical techniques. The results indicate surface structural transformations from metastable FeO(111) and O-terminated Fe(2)O(3)(0001) to Fe(3)O(4)(111) films, respectively. The former depends strongl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 32 publications
3
33
0
Order By: Relevance
“…in Fig. 2(d), which are evidence to Fe 3+ [23][24][25]. The XPS results presented that Zn and Fe elements existed in the synthesized samples were in the forms of Zn 2+ and Fe 3+ , respectively, which corresponding to the characterization of the above XRD pattern.…”
Section: Composition and Morphologymentioning
confidence: 63%
“…in Fig. 2(d), which are evidence to Fe 3+ [23][24][25]. The XPS results presented that Zn and Fe elements existed in the synthesized samples were in the forms of Zn 2+ and Fe 3+ , respectively, which corresponding to the characterization of the above XRD pattern.…”
Section: Composition and Morphologymentioning
confidence: 63%
“…The O-rich termination (B) was predicted to be thermodynamically more stable than the stoichiometric termination using GGA (Generalized Gradient Approximation) [39,31] and was confirmed by the structure characterizations [25,28,38]. However, a reverse stability order was proposed when considering the strongly-correlated effects [21].…”
Section: Surface (0 0 1)mentioning
confidence: 91%
“…Hematite (0 0 1) surface is coherent with magnetite (1 1 1) and wustite (1 1 1) surfaces. It has been found that the surface phase transformations are sensitive to the temperature and pressure of O 2 [25]. The reduced surface phases (magnetite (1 1 1) and wustite (1 1 1)) should be formed and sustained from high-temperature processes where they are thermodynamically more stable than hematite.…”
Section: Surface (0 0 1)mentioning
confidence: 99%
“…This was explained as follows: during annealing at 200 °C , electrons and cations are transported to the surface of the sample; the Fe 3+ ions present near the surface are reduced to Fe 2+ . In addition, Xue et al [17] reported that Fe 2 O 3 can be transformed to Fe 3 O 4 after annealing at 800 K without ambient oxygen. Therefore, regarding the electronic properties of the surface overlayer after the Up1 scan to 339 °C , the outermost region contained accumulated electrons, which did not lead to emission.…”
Section: Effect Of Oxide Components and Activationmentioning
confidence: 99%